ON Gd-DISTANCE OF A GRAPH - et al., V.Maheswari (International Journal of Advanced Science and Technology, 2019)
The concept of Gd- distance between any two vertices in a graph is introduced by V.Maheswari and M.Joice Mabel in [4]. In this paper, we introduce Gd-distance of a graph. We compute the Gd-distance of a path, cycle, complete graph, complete bipartite graph, grid graph, sun, star, wheel and line graph. Also we determine the Gd-distance for some shadow graphs.